x - y = 8
Answer:
C. (5, -3)
Step-by-step explanation:
4x + 3y = 11
x - y = 8 (multiply by 3) --> 3x - 3y = 24
4x + 3y = 11
3x - 3y = 24
---------------------add
7x = 35
x = 5
5 - y = 8
y = 5 - 8
y = -3
(5, -3)
Answer:
C. (5, -3)
Step-by-step explanation:
Rewrite the first equation.
Multiply the second equation by 3 and write it under the first equation.
4x + 3y = 11
3x - 3y = 24
Now add the equations.
7x = 35
Divide both sides by 7.
x = 5
Substitute 5 for x in the original first equation:
4(5) + 3y = 11
20 + 3y = 11
3y = -9
y = -3
Solution: (5, -3)
Answer:
5/-4
Step-by-step explanation:
rise over run
y2-y1/x2-x1
2-(-3)/(-4)-0